PENGEFEKTIFAN PEMBELAJARAN BIOLOGI MELALUI METODE STBCT GUNA MENINGKATKAN CAPAIAN BELAJAR SISWA DI SMAN 1 BUNGO - sugihartini sugihartini (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
This study aims to improve learning outcomes in biology through the application of the SQ3R (Survey, Question, Read, Recite, Review) learning method. This research is a classroom action research (CAR) which is carried out in four stages, namely planning, implementing actions, observing and reflecting. The subjects of this study were students of class XI MIPA 5 SMAN 1 Bungo. Data collection techniques were carried out by documentation, interviews, observations and tests. The success of CAR is seen from the increase in classical learning completeness in the discussion value from 76.67% in the first cycle to 90.9% in the second cycle. And classical learning completeness on the evaluation value from 75.75% in the first cycle to 93.93% in the second cycle. In addition, there was also an increase in the average student learning outcomes. With evidence that in the first cycle the average value of the class on the discussion value was 62.2, in the second cycle there was an increase of 75.72. While the average value of the evaluation of the first cycle of 66.25 has increased to 76.30. So it can be concluded that the SQ3R learning method can improve students' biology learning outcomes in class XI MIPA 5 SMAN 1 Bungo